Голавль бассейна верхнего Днестра - Опалатенко, Л.К. (Гидробиологический журнал, 1966)
Наши материалы касаются морфометрической и частично биологической характеристики голавля, а также значения его в промысле. The characteristics of Leuciscus cephalus (L.) of the upper Dniester basin are given with respect to meristic and plastic properties, and these data are used for a biometric analysis of fish of both sexes. The results of the analysis indicate that the morphological characters of this species are relatively stable, as compared with those of L. cephalus of other basins. L. cephalus occurs everywhere in the Dniester basin, but most frequently in the main channel and large tributaries. It reproduces in May —June, producing about 26,400 roe corns on the average. L. cephalus grows uniformly only in the course of the first four years; at the age of three years it attains an average length of 20.4 cm, but beginning with the fifth year its growth gradually slows up. The number of fish in the L. cephalus school is not large; the fish does not enter into the main catch. The numbers of this species should be increased by stopping the ejection into the Dniester of industrial waste waters, and by carrying out measures for the protection of this fish during the period of reproduction.